Development of Global Warming E-Module Based on Socio Scientific Issues (SSI) to Improve Students' Critical Thinking Skills and Sustainability Awareness - Adinda Dian Utami; Surti Kurniasih; Indarini Dwi Pursitasari (Jurnal Penelitian Pendidikan IPA, 2023)
Science education has a role in realising the global vision to encourage the achievement of 21st century competencies. One of them is by implementing science learning with the Socio Scientific Issues (SSI) context. The Research and Development study aims to produce a global warming E-Module based on Socio Scientific Issues (SSI) to improve students' critical thinking skills and sustainability awareness. The research and development design used is the ADDIE (Analysis Design Development Implementation Evaluation) model design. The research subjects for e-module implementation were 38 students of class X SMA Negeri 3 Cibinong. Research data were obtained through e-module validation questionnaire, critical thinking skills essay questions, sustainability awareness questionnaire, and student response questionnaire.Â  Data analysis techniques using shapiro wilk, paired sample t-test. Based on the research results, it can be concluded that the SSI-based global warming e-module is valid/suitable for use in terms of feasibility (content, presentation and language), as well as in terms of media with the percentages respectively being 91% and 97%. The CVI results related to the feasibility of the e-module are 0.99 (valid). Learning using the SSI-based global warming e-module can improve students' critical thinking skills in the high category with an average score of N-Gain critical thinking skills of 0.78. Learning using the SSI-based global warming e-module can increase students' sustainability awareness in the medium category with an average N-Gain sustainability awareness score of 0.45. Student responses to the SSI-based global warming e-module were very good with an average score percentage of 91%.